Assessing the royal woodcarving motifs parameter using fractal dimension in Istana Balai Besar and Istana Tengku Long - Normaisarah Mohd Rosdi (2024)
Woodcarving is a cultural and artistically significant traditional craft, and understanding the aspects that contribute to the intricacy of woodcarving panels can shed light on the skills and craftsmanship involved in their creation. The study topic arises from a significant gap in scholarly comprehension of the intricate complexities associated with woodcarving patterns, particularly in the significant context of traditional timber royal palaces. This gap motivates an investigation into the application of Fractal Dimension Analysis (FDA) as a technique to comprehensively examine and measure the complicated composition of these intricate artistic works. By using the FDA, researchers seek to explore further into the structural complexity and aesthetic details of woodcarving panels, revealing light on the underlying patterns and proportions that contribute to their visual richness and cultural value in royal architectural settings. Hence, the aim of this research is to identify the complex panel and its characteristics from the royal timber palaces of Istana Balai Besar, Kelantan and Istana Tengku Long, Terengganu. A mixed methods strategy integrating qualitative and quantitative techniques was used to attain the research aims. The application of Fractal Dimension by Mandelbrot as a quantitative tool provides a fresh technique for assessing the complexity of woodcarving designs. The findings from the study revealed that elements of woodcarving in a composition, the techniques employed in creating the woodcarving panel and the skills of the woodcarver contribute to the level of complexity in a panel composition. The findings can be used to guide future research into woodcarving processes, cultural heritage preservation, and design analysis.